PENERAPAN APLIKASI PEMBERKASAN ARSIP DINAMIS DAN STATIS DI KANTOR PELAYANAN PAJAK PRATAMA KARANGANYAR - Noviana Putri; Cicilia Dyah S. Indrawati; Anton Subarno (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
This study aims to determine the implementation of dynamic and static filing applications in the Service Section at Pratama Tax Office Karanganyar. This research was conducted at Pratama Tax Office Karanganyar. The sampling of this research is using purposive sampling and snowball sampling technique. Data collection techniques with observation, interviews, and documentation. The validity of the data was obtained by triangulation of sources and methods. The data analysis technique uses interactive model data analysis. The results obtained: (1) the application of dynamic and static filing applications facilitates file storage to be neatly organized in one system, facilitates file retrieval, and makes it easier for officers to monitor files, (2) obstacles in implementing dynamic and static filing applications are unstable computer servers and application menus need to be added, and (3) the efforts to overcome obstacles in implementing dynamic and static filing applications are coordinating with system administration for server repairs and submitting proposals for adding file application menus.